Peningkatan Hasil Belajar Menulis Teks Deskriptif Sederhana melalui Model Pembelajaran Kooperatif STAD - Sri Lahir (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve Learning Achievement in Writing Simple Descriptive Texts Through the STAD Cooperative Learning Model for Class IXB Negeri 6 Sukoharjo Students in Semester 1 of the 2022/2023 Academic Year